Agricultural Organochlorine Pesticides Residues In Surface And Groundwaters Of The Negro River Basin (North Patagonia) - Funes, Aimé Itati (2023)
In the present research, we studied the occurrence of a total of 16 organochloride pesticides (OCs) forbidden by the Convention, including α-HCH, β-HCH, γ-HCH, δ-HCH, heptachlor, aldrin, heptachlor epoxide, dieldrin, endrin, endrin aldehyde, pp´-DDT, pp´-DDE, and pp´-DDD, as well as endosulfan and its metabolites (α-endosulfan, β-endosulfan, endosulfan sulfate) in the surface and ground waters of the Negro River basin in seven sites with different land uses. Our results concluded that the physicochemical parameters determined that groundwater was unsuitable for human consumption due to high pH and low DO. The mean value of the sum of the concentrations of the OCs analyzed for dissolved pesticides in groundwater samples was 2.35 ng L-1, and only aldrin was detected at the outlet of the river area in the order of 5.44 ng L-1. In contrast, no pesticides were detected in waters characterized by mixing processes with seawater. As a result, chlorinated cyclodiene insecticides, like heptachlor, β-endosulfan, and aldrin, were detected in groundwater samples. Only aldrin was detected in the surface waters of one site (the river outlet). However, most of these samples' OCs were